Peg-based temperature sensitive nanoparticle synthesis and their use in protein adsorption - Guldem Utkan (Archive of Biomedical Science and Engineering - Peertechz Publications, 2018)
In this study, temperature sensitive polymeric nanoparticles were prepared by emulsifier free emulsion polymerization. N-isopropylacrylamide (NIPA) has been used as main monomer to give temperature sensitivity and poly(ethyleneglycol) ethyl ether methacrylate (PEG-EEM) has been added to recipes as comonomer to aid in particle formation. The effect of NIPA, PEG-EEM and crosslinker content on particle size has been investigated. Temperature sensitivity or lower critical solution temperature (LCST) of the nanoparticles has been followed by Zeta Sizer as change in particle size. In order to determine the protein adsorption capacity of nanoparticles, adsorption experiments have been investigated as a function of temperature and PEG-EEM amount. The results showed that the adsorption capacity of both NIPA and NIPA/PEG-EEM latexes was increased similarly with the increase in temperature. However, amount of BSA adsorbed on NIPA/PEG-EEM particles has been slightly higher than that of for NIPA alone. This study showed that synthesized NIPA/PEG-EEM nanoparticles would be a good candidate for the further studies on protein adsorption.